At the water table: Seeking the trace in research writing - Thesen, Lucia (Critical Studies in Teaching and Learning, 2025)
This paper describes a process of concept development, written in memory of Elmarie Costandius, who I learnt from in a series of workshops to reconfigure scholarship. Elmarie's humble way of working with concepts in art-based inquiry, with a strong commitment to social justice, widened and deepened my interest in the relationship between knowledge-making and writing – a great interest to me after decades of facilitating writers’ circles for postgraduate scholars. Involvement in the writers' circle, and the inspiration of Elmarie and the scholars around her, alert me to the possibilities of more responsive, situated, tentative ways of knowing that honour the traces of knowledge-making. These traces are an alternative to the limitations imposed by omniscient, conquest notions of knowledge and how they are inscribed in conventional genres of research.